1952
DOI: 10.1039/jr9520003503
|View full text |Cite
|
Sign up to set email alerts
|

671. The carboxylation of resorcinol and the separation of β-and γ-resorcylic acid by ion-exchange chromatography

Abstract: Yields of y-resorcylic acid afforded by various modifications of the Kolbe-Schmitt reaction have been explored and methods of separating the acid from the accompanying @-isomer have been studied. Selective elution of the acids from a column of an anion-exchange resin in the chloride form with solutions of hydrochloric acid in water or aqueous alcohol effects complete separation.A process for the partial conversion of Pinto y-resorcylic acid is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Whereas a strong increase of yield with rising temperature for very short residence times is observed, this rise decreases for longer residence times, reaches a maximum and then decreases with rising temperature. This might be due to the preferred formation of the byproduct 2,6-DHBA or c-resorcylic acid at higher temperatures and longer residence times as reported in the literature [44,45] (Scheme 2).…”
Section: Temperature Dependence Of Yield and Stymentioning
confidence: 90%
See 1 more Smart Citation
“…Whereas a strong increase of yield with rising temperature for very short residence times is observed, this rise decreases for longer residence times, reaches a maximum and then decreases with rising temperature. This might be due to the preferred formation of the byproduct 2,6-DHBA or c-resorcylic acid at higher temperatures and longer residence times as reported in the literature [44,45] (Scheme 2).…”
Section: Temperature Dependence Of Yield and Stymentioning
confidence: 90%
“…Hale et al [44] observed the formation of considerable amounts of 2,6-DHBA and resorcinol from the monopotassium salt of 2,4-DHBA and the liberation of carbon dioxide when it was heated in an aqueous solution at 200°C. In contrast to 2,4-DHBA, the decarboxylation of 2,6-DHBA starts already above 80°C, i.e., at still higher temperatures, it will be in significant parts decomposed to resorcinol, which could not be distinguished from the starting material by HPLC analysis.…”
Section: Temperature Dependence Of Yield and Stymentioning
confidence: 98%
“…25 %), which was not obtained in any other of the Kolbe-Schmitt reactions carried out in this study. It is known that decarboxylation takes place at elevated temperature, which proceeds via 2,6-dihydroxybenzoic acid [39]. The nature of this side product was ascertained by comparison of the retention time with a commercially obtained sample of 2,6-dihydroxybenzoic acid.…”
Section: Kolbe-schmitt Synthesis Using Ionic Liquidsmentioning
confidence: 99%
“…A byproduct 2,6-dihydroxy benzoic acid is formed, 63 which is favoured at high temperatures and long residence times. 64 Due to continuous processing and to its small dimensions the experimental set up offers the capability to improve selectivity. The process variant of the Kolbe-Schmitt synthesis used here is different from that used for the synthesis of monohydroxycarboxylic acids like acetylsalicylic acid which is a gassolid reaction performed in pressurised vessels (autoclaves) at high temperatures.…”
Section: Current Implementation Of Novel Process Windows Into Chemica...mentioning
confidence: 99%